2007
DOI: 10.1111/j.1461-0248.2007.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape heterogeneity shapes predation in a newly restored predator–prey system

Abstract: Because some native ungulates have lived without top predators for generations, it has been uncertain whether runaway predation would occur when predators are newly restored to these systems. We show that landscape features and vegetation, which influence predator detection and capture of prey, shape large-scale patterns of predation in a newly restored predator-prey system. We analysed the spatial distribution of wolf (Canis lupus) predation on elk (Cervus elaphus) on the Northern Range of Yellowstone Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
309
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(326 citation statements)
references
References 55 publications
10
309
3
1
Order By: Relevance
“…In addition, early studies on the BMTCH reported that wolves scared herbivores away from riparian areas, which reduced herbivory on trees and ultimately caused increased tree growth (Ripple and Beschta, 2004;Beschta and Ripple, 2007). Not only did these earlier studies incorrectly identify areas of high predation risk (Creel et al, 2005;Kauffman et al, 2007;Kauffman et al, 2010;Winnie, 2012), but they also failed to consider more parsimonious explanations for increased tree growth in riparian areas, such as the height of the local water table (Bilyeu et al, 2008;Kauffman et al, 2013). MacNulty et al (2016;pg.…”
Section: Alternative Hypotheses Are Seldom Testedmentioning
confidence: 99%
“…In addition, early studies on the BMTCH reported that wolves scared herbivores away from riparian areas, which reduced herbivory on trees and ultimately caused increased tree growth (Ripple and Beschta, 2004;Beschta and Ripple, 2007). Not only did these earlier studies incorrectly identify areas of high predation risk (Creel et al, 2005;Kauffman et al, 2007;Kauffman et al, 2010;Winnie, 2012), but they also failed to consider more parsimonious explanations for increased tree growth in riparian areas, such as the height of the local water table (Bilyeu et al, 2008;Kauffman et al, 2013). MacNulty et al (2016;pg.…”
Section: Alternative Hypotheses Are Seldom Testedmentioning
confidence: 99%
“…2005; Kauffman et al. 2007), and prey species can therefore be expected to alter their response to both mortality and predator encounter risk with environmental variation across landscapes. Concurrently, prey species can make use of the environment to avoid detection and/or escape predators (Creel et al.…”
Section: Introductionmentioning
confidence: 99%
“…All those landscape characteristics are known drivers of wolf habitat selection and their relationship with prey (Mao et al 2005, Kauffman et al 2007, Hebblewhite and Merrill 2008, Houle et al 2010, Latham et al 2011, Milakovic et al 2011, Whittington et al 2011 Mao et al (2005). This coverage represents the percentage of openhabitat pixels at a distance smaller than 400 m from each grid cell (25-m cell resolution).…”
Section: Data Sourcesmentioning
confidence: 99%
“…First, for those three years we had information on the spatial distribution of elk (Cervus elaphus), which are the primary prey for these wolves (Smith et al 2004). The sites where wolves kill prey seem to be influenced, not so much by the presence of elk, but instead by the presense of habitats that increase the probability of a successful kill (Bergman et al 2006, Kauffman et al 2007). Nevertheless, the extent to which wolves' habitat preferences correspond with overall elk distribution remains unclear.…”
Section: Introductionmentioning
confidence: 99%